Who are the economists Germany listens to? The social structure of inluential German economists - Stephan Puehringer; Karl Beyer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
Building on recent work on the political and societal impact of economics and distinct economists, respectively, this chapter aims to examine individual, research and institutional characteristics as well as existing professional networks of what are considered to be "influential economists" in Germany. For the purpose of identifying the most influential economists, we make use of the popular impact ranking of the German newspaper Frankfurter Allgemeine Zeitung (FAZ) entitled "The economists, Germany listens to" ("Auf diese Ökonomen hört das Land"), which distinguishes research, media and political impact. Through biographical research and the application of social network analysis we show that most influential economists are involved in co-authorship and/or institutional networks and that there are substantial connections to different levels of public governance. We find a tremendous gender bias within the sample as well as some hints for internationalization and division of labor. Our analysis moreover indicates a much less hierarchical structure of the Germanspeaking economics profession when compared to the U.S. A breakdown also reveals some considerable differences between the different impact rankings. We find that while a striking majority of media and policy advice economists have connections to (inter)national public governance bodies, only a minority of research economists have. Furthermore, the ordoliberal bias, which is a crucial feature of the German economics profession, is mainly restricted to media and policy advice economists. Finally, our analysis indicates the central role of (partly also geographically organized) research hubs among influential research economists.
Keywords: A11; A14; N01; 330; political and societal impact of economists; German economics; socio-economics; professional networks; social network analysis; biographical research; co-authorship; power in economics